Iamblichus and the foundations of late platonism - Afonasin, E. V.; Dillon, John M.; Finamore, John F., 1951- (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2012)
Iamblichus of Chalcis (c. 240-c. 325 C.E.), successor to Plotinus and Porphyry, gave new life to Neoplatonism with his many philosophical and religious refinements. Once regarded as a religio-magical quack, Iamblichus is now seen as a philosophical innovator who harmonized not only Platonic philosophy with religious ritual but also Platonism with the ancient philosophical and religious tradition. Building on recent scholarship on Iamblichean philosophy, the ten papers in this volume explore various aspects of Iamblichus' oeuvre. These papers help show that Iamblichus re-invented Neoplatonism and made it the major school of philosophy for centuries after his death.